Vitamin E is Necessary to Protect Neural Crest Cells in Developing Zebrafish Embryos. (29th May 2020) - Head, Brian; Du, Jane La; Tanguay, Robyn; Kioussi, Chrissa; Traber, Maret
Abstract: Objectives: Vitamin E (VitE) deficiency causes vertebrate embryonic lethality. The alpha-tocopherol transfer protein ( Ttpa ) likely regulates VitE distribution in the early zebrafish embryo because Ttpa knockdown causes impaired nervous system development and embryonic death by 15–18 hours post-fertilization (hpf). We propose that VitE is necessary for normal brain and peripheral nervous system development. Methods: Zebrafish embryos are obtained from adults fed either VitE sufficient (E+) or deficient (E–) diets for at least 80 days. Embryos at 12 and 24 hpf are subjected to RNA whole mount in situ hybridization (WISH). RNA is also collected from embryos at 12, 18 and 24 hpf for RT-qPCR of specific targets. Results: At 12 hpf, the midbrain-hindbrain boundary and otic placodes are malformed in E– embryos, as shown by Pax2a expression. Similarly, Sox10 expression shows that E– embryos lack clear neural plate borders. Nonetheless, in 12 hpf E + and E− embryos Ttpa is localized similarly throughout the nervous system. Pax2a expression initiates collagen formation in the developing notochord. Collagen genes, col2a1a and col9a2, expression patterns showed abnormal notochord structures in 24 hpf E– embryos. At 24 hpf in E + embryos, Sox10 expressing-neural crest cells are localized both in the central nervous system and dorsal root ganglia (DRG), while the Sox10 signal is diminished in E– embryos in both the DRG and early enteric nervous system. At 24 hpf, Ttpa expression outlines the brain ventricle borders; critically E– embryos show reduced Ttpa signal and impaired ventricle closing. Gene expression by qPCR will be used to confirm these results. Conclusions: This VitE deficient embryo model suggests that the carefully programmed development of the nervous system is distorted due to lack of adequate VitE. Thus, Ttpa and VitE are critical molecules for neural plate and neural tube formation, and neural crest cell migration. Funding Sources: The authors received no specific funding for this work.